Avaliação físico-química e potencial remineralizador de adesivos autocondicionantes experimentais com CPP-ACP - Lima, Karlos Eduardo Rodrigues (2024)
Minimally invasive dentistry has advanced with restorative treatment proposals that involve selective removal of carious tissue. However, effective adhesion to demineralized dentin remains a significant challenge compared to sound dentin. A promising approach to overcoming this limitation is the integration of new technologies that strengthen the resin-dentin interface, such as adding remineralizing properties through bioactive restorative materials. This study aimed to evaluate the physicochemical properties, bond strength, and emineralization potential of experimental self-etch adhesives incorporated with hydrolyzed tri- and poly-metaphosphate + polyacrylic acid (TMP+PAA) in the primer and/or casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) in the bond applied to artificially demineralized dentin (ADD). The experimental groups were divided into four categories according to the adhesive formulation used: control, TMP+PAA, CPP-ACP, and TMP+PAA/CPP-ACP. The evaluation of the adhesive systems' properties included analysis of the degree of conversion (DC) by micro-Raman spectroscopy (n=3), assessed immediately, evaluation of the modulus of elasticity (ME) [n=12] by three-point bending test, and determination of water sorption (S) and solubility (SL) [n=12], assessed immediately and after 6 months. Additionally, to evaluate the remineralization potential, ADD samples were obtained through pH cycling in the mid-dentin of human third molars. After the restorative procedure, the teeth were sectioned into 2mm thick slices for Knoop microhardness analysis (n=3) immediately and after three months. Furthermore, dentin-resin samples were obtained from previously restored teeth for the microtensile test (n=8) immediately and after 10,000 thermocycling cycles. For statistical analysis, the DC data were subjected to one-way ANOVA, while S, SL, and ME data were analyzed by two-way ANOVA, and the microhardness data were analyzed by repeated measures ANOVA, followed by Tukey's post-hoc test (p<0.05). Overall, the incorporation of TMP+PAA and/or CPP-ACP did not adversely affect the properties of DC, SL, and ME (p>0.05). However, the TMP+PAA and CPP-ACP groups showed higher S (p<0.05). Moreover, these systems formulated with TMP+PAA and/or CPP-ACP demonstrated significant potential to promote dentin remineralization, especially in the underlying dentin and at depths of 30 and 70 μm below the surface, significantly improving both the substrate microhardness (p<0.05) and bond strength to ADD (p<0.001), immediately and after aging. Thus, it is concluded that the proposed experimental adhesive with TMP+PAA in the primer and CPP-ACP in the bond improved microhardness and bond strength to ADD, even after aging, without compromising the properties of the adhesive system.